2005
DOI: 10.1118/1.1869852
|View full text |Cite
|
Sign up to set email alerts
|

Four‐dimensional computed tomography: Image formation and clinical protocol

Abstract: Respiratory motion can introduce significant errors in radiotherapy. Conventional CT scans as commonly used for treatment planning can include severe motion artifacts that result from interplay effects between the advancing scan plane and object motion. To explicitly include organ/target motion in treatment planning and delivery, time-resolved CT data acquisition (4D Computed Tomography) is needed. 4DCT can be accomplished by oversampled CT data acquisition at each slice. During several CT tube rotations proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
319
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(332 citation statements)
references
References 16 publications
(14 reference statements)
2
319
0
6
Order By: Relevance
“…CT data are reconstructed with a slice thickness of 2 mm. Scans are acquired with an X‐ray tube rotation time of 0.5 s. These parameters are close to those reported in the study by Rietzel et al ( 30 ) who concluded that the accuracy of 4D CT images is one CT slice thickness. Although additional setup error may be introduced in the process of matching the CBCT to DRR generated by average image of 4D CT, the total uncertainties can be limited within few millimeters.…”
Section: Resultssupporting
confidence: 69%
“…CT data are reconstructed with a slice thickness of 2 mm. Scans are acquired with an X‐ray tube rotation time of 0.5 s. These parameters are close to those reported in the study by Rietzel et al ( 30 ) who concluded that the accuracy of 4D CT images is one CT slice thickness. Although additional setup error may be introduced in the process of matching the CBCT to DRR generated by average image of 4D CT, the total uncertainties can be limited within few millimeters.…”
Section: Resultssupporting
confidence: 69%
“…The use of 4D CT scanning is not only able to determine the intrafractional tumor motion, 6 , 8 but also to eliminate respiration motion artifacts 9 , 11 . Moreover, the size of PTVs of lung cancers can be reduced using the technique of 4D CT compared with the technique of 3D CT 5 , 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The time stamps of the reconstructed CT images and the measured respiratory signal of the patient are retrospectively matched. The reconstructed images are sorted either by the phase (2) or by the displacement, (3) which are then stacked to create a three‐dimensional (3D) image of the patient for each image bin. A 4D image set is then reconstructed by viewing the 3D images in sequence for each image bin.…”
Section: Introductionmentioning
confidence: 99%